TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION - Gendis Nadira Dwiningtiyas; Dedi Sofyan; Hilda Puspita (JALL (Journal of Applied Linguistics and Literacy), 2020)
This research aimed to figure out the strategies used by the English teachers in teaching reading and how they applied the strategies. This research was designed as descriptive qualitative research. The research was conducted at Junior High School 09 Bengkulu City. Participants of the research were two English teachers who teach in second grade of that school. Each English teacher had eigh meetings that observed by the researcher. The instruments of the research were strategies checklist and interview. The instruments were used to figure out the strategies used and how the English teachers applied the strategies in teaching reading comprehension. The result of the data were analyzed and broken down into three stages; they were Data Reduction, Data Display, and Drawing Conclusion or Interpretation. The result showed that the teacher one used several strategies in teaching reading comprehension. The strategies were brainstorming, reading aloud, and asking for specific information. While the teacher two used nine strategies. They were encouraging the use of dictionaries, reading aloud, reread for checking comprehension, evaluating comprehension in particular tasks, and asking questions for specific information. Both teachers applied and combined the strategies divided into three stages of teaching reading comprehension. The stages were pre-reading stage, while reading stage, and post reading stage. The strategies applied were very effective in teaching reading comprehension in that school. It was proven by the students’ motivation, students’ attention, and teachers’ ease in teaching and learning process. Keywords: Reading Comprehension and Teachers’ Strategies.